Sustainability of Building Materials Used in Traditional Local Architecture: The Case of Villa Selene in Al-Khums as a Model for Contemporary Construction" (Comprehensive Journal of Science, 2025)
Traditional buildings embody the dialogue between humans and nature in all its dimensions. As human life continues and extends from the past, architectural heritage symbols serve as markers of present-day identity. Traditional architecture in Libya, across its diverse regions, is rich in architectural elements and components that have accompanied its emergence and evolution. Each of these elements was shaped by a specific philosophy and design rationale.The building materials used in historic traditional structures have played a significant role in achieving thermal and environmental comfort. This study aims to highlight the sustainability of materials used in traditional buildings and to evaluate their potential as a guide for contemporary construction practices in modern cities.The focus of this study is on the sustainability of building materials in historic coastal architecture and the lack of their application in contemporary construction. The importance of this research lies in proposing a clear strategy for selecting building materials in modern architecture based on sustainability principles.The study adopts a descriptive-analytical methodology, case study approach of traditional buildings, and a historical perspective. Findings indicate that the materials used in traditional coastal dwellings successfully achieved core principles of sustainability.
Keywords: Sustainability – Architectural Heritage – Building Materials – Traditional Architecture